Occupational advice to help people return to work following lower limb arthroplasty: the OPAL intervention mapping study - Paul Baker; Carol Coole; Avril Drummond; Sayeed Khan; Catriona McDaid; Catherine Hewitt; Lucksy Kottam; Sarah Ronaldson; Elizabeth Coleman; David A McDonald; Fiona Nouri; Melanie Narayanasamy; et al. (Health Technology Assessment, 2020)
Background: Hip and knee replacements are regularly carried out for patients who work. There is little evidence about these patients’ needs and the factors influencing their return to work. There is a paucity of guidance to help patients return to work after surgery and a need for structured occupational advice to enable them to return to work safely and effectively. Objectives: To develop an occupational advice intervention to support early recovery to usual activities including work that is tailored to the requirements of patients undergoing hip or knee replacements. To test the acceptability, practicality and feasibility of this intervention within current care frameworks. Design: An intervention mapping approach was used to develop the intervention. The research methods employed were rapid evidence synthesis, qualitative interviews with patients and stakeholders, a prospective cohort study, a survey of clinical practice and a modified Delphi consensus process. The developed intervention was implemented and assessed during the final feasibility stage of the intervention mapping process. Setting: Orthopaedic departments in NHS secondary care. Participants: Patients who were in work and intending to return to work following primary elective hip or knee replacement surgery, health-care professionals and employers. Interventions: Occupational advice intervention. Main outcome measures: Development of an occupational advice intervention, fidelity of the developed intervention when delivered in a clinical setting, patient and clinician perspectives of the intervention and preliminary assessments of intervention effectiveness and cost. Results: A cohort study (154 patients), 110 stakeholder interviews, a survey of practice (152 respondents) and evidence synthesis provided the necessary information to develop the intervention. The intervention included information resources, a personalised return-to-work plan and co-ordination from the health-care team to support the delivery of 13 patient and 20 staff performance objectives. To support delivery, a range of tools (e.g. occupational checklists, patient workbooks and employer information), roles (e.g. return-to-work co-ordinator) and training resources were created. Feasibility was assessed for 21 of the 26 patients recruited from three NHS trusts. Adherence to the defined performance objectives was 75% for patient performance objectives and 74% for staff performance objectives. The intervention was generally well received, although the short time frame available for implementation and concurrent research evaluation led to some confusion among patients and those delivering the intervention regarding its purpose and the roles and responsibilities of key staff. Limitations: Implementation and uptake of the intervention was not standardised and was limited by the study time frame. Evaluation of the intervention involved a small number of patients, which limited the ability to assess it. Conclusions: The developed occupational advice intervention supports best practice. Evaluation demonstrated good rates of adherence against defined performance objectives. However, a number of operational and implementation issues require further attention. Future work: The intervention warrants a randomised controlled trial to assess its clinical effectiveness and cost-effectiveness to improve rates and timing of sustained return to work after surgery. This research should include the development of a robust implementation strategy to ensure that adoption is sustained. Study registration: Current Controlled Trials ISRCTN27426982 and PROSPERO CRD42016045235. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 24, No. 45. See the NIHR Journals Library website for further project information.